Computational analysis on the thermal and mechanical properties of thin film solar cells. (2021) - Roy, Sudesna; Baruah, Mriganka Sekhar; Sahu, Sasmita; Nayak, Bijaya Bijeta
Abstract: Solar cells are valuable source of alternative energy that is environmental friendly and involves utilization of a free and abundant natural resource. The revolution of utilization of solar cell materials has undergone huge many changes since the time of its inception. The solar cell material may be classified into first, second and third generations. The first generation include the monocrystalline and polycrystalline silicon in the solar cell, whereas the second generation include the thin film photovoltaics as the solar cell materials. The present market in solar cells in greatly divided between these two generations of materials which differ in their price, conversion efficiency as well as their ease of manufacture; all the factors that determines its commercial viability. The third generation solar cells though still in its nascent stage of development shows good promise of improving the future technology drastically. This paper aims to compare the thin film solar cell materials with the conventional mono and polycrystalline silicon solar cells. In this regard a literature survey of the thin film solar cells show that the thermal stresses that develop in them during thermal cycling are significant to cause failure. Hence this work compares the thermal stresses in different thin film solar materials by a finite element analysis using ANSYS software. The thermal heat flux, total deformation, thermal stress and strain were calculated and compared. It was observed that amorphous silicon thin films on glass substrate have the highest thermal heat flux, lowest deformation, thermal stress and strain on the film-substrate interface at elevated temperatures. Amorphous silicon thin films seem to be an alternate to monocrystalline and polycrystalline silicon, where the thin film although has lower efficiency has reduced price and increased ease of manufacturing, making it viable for the commercial market.